SISTEM PENANGANAN PENGADUAN BERBASIS E-GOVERNMENT PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN KENDAL - Muhammad Fatchuriza; Teguh Adi Prasojo (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2021)
The purpose of this study is to determine the extent of the handling of public complaints management based on E-government in Kendal Regency and the response of the Kendal Regency Government to complaints from the public. This study used a qualitative descriptive research method, while data collection was carried out in three ways, namely observation, interviews, namely interviews with experts or people who understand topic to be researched and documentation study. The results showed firstly that E-government-based complaint handling system at UP4 of the Communication and Informatics Office of Kendal Regency was running optimally. The indicators that can be seen are as of February 2019 as many as 1338 complaints that were submitted to the Public Service Complaints Management Unit (UP4) 1248 have been processed. Second, in the context of implementing e-government in managing complaints, it is included in the scope of Government to Citizens (Government to Society) and also includes the use of Government to Employees services. Third, the types of e-government services in Indrajit (2004: 29-32) are described as divided into three main classes, namely: publish category, interact category, and transact category. In compalint handling system based on e-gove at UP4 Kendal district, it is included in the interact class category, because there has been a two-way communication and interaction relationship between the government and the community. The Influencing Factors 1. From government agencies, a) complaint distribution flow b) required maintenance costs. c) Internet Network. 2. From the community, a) Servers that often have problems, b) Less feedback